1186 Developing And Testing A Web-based Provider Training For Cognitive Behavioral Therapy Of Insomnia. (27th May 2020) - Taylor, D; Bunnell, B; Calhoun, C; Pruiksma, K; Dietch, J; Wardle-Pinkston, S; Milanak, M; Rheingold, A; Simmons, R; Peterson, A; Morin, C; Ruggiero, K; et al.
Abstract: Introduction: Chronic insomnia is a common, debilitating disorder and a risk factor for significant medical morbidity, mental health problems, and workplace difficulties. Cognitive behavioral therapy for insomnia (CBT-I) is the gold standard treatment for insomnia. However, few providers are trained in CBT-I, in part due to a bottleneck in training availability and the time and cost associated with current training platforms. To address this training deficit, our team developed and evaluated CBTI web .org, a web-based provider training course for CBT-I. Methods: Feedback from alpha- and beta-testing of CBTI web .org was collected and used to optimize course content and functionality. Then, a comparison study was conducted in which licensed providers were randomized to complete either the online CBTI web .org course (n=21) or an in-person CBT-I training (n=23). During all phases of development, providers completed a Computer System Usability Questionnaire (CSUQ), investigator-developed website usability and content questionnaires, and pre/post-training competency assessments. Results: Independent samples t -tests indicated significant improvements in CSUQ, and website usability and content questionnaires responses from alpha- to beta-testing (all p s < .05). Linear mixed-effects modeling revealed significant within-subject increases in knowledge acquisition ( F (34.7) = 65.4, p < 0.001; baseline = 69% correct, post-training = 92% correct) when collapsed across in-person and web-based groups. The interaction group by time interaction was non-significant ( F (34.7) = 1.7, p = 0.204), indicating similar gains in knowledge (i.e., equivalence) between the in-person and the CBTI web .org training formats. Conclusion: Alpha and beta testers of CBTI web .org reported high levels of satisfaction while also noting areas for improvement, which were used to update the site. Findings suggest the final CBTI web .org product successfully trained clinicians compared to an in-person workshop, given knowledge acquisition improvements. CBTI web .org is an efficient and effective training platform for clinicians to gain knowledge and competence in the most effective treatment for insomnia. Support: W81XWH-17-1-0165